Breathing makes it better : a book for sad days, mad days, glad days, and all the feelings in-between - Willard, Christopher (Psychologist); O'Leary, Wendy; Marley, Alea (Boulder, Colorado : Bala Kids, 2019)
"Read aloud and breathe along with this sweet story teaching children how to navigate powerful emotions like anger, fear, sadness, confusion, anxiety, and loneliness. With rhythmic writing and engaging illustrations, Breathing Makes It Better guides children to breathe through their feelings and find calm with recurring cues to stop and take a breath. Simple guided practices, like imagining you are a tree blowing in the wind, follow each story to teach children how to apply mindfulness techniques when they need them the most" --
Age: 4-8.
660L
Keywords: Emotions in children -- Juvenile literature; Breathing exercises -- Juvenile literature; Respiration -- Juvenile literature; Mindfulness (Psychology) -- Juvenile literature; Instructional and educational works; Picture books